Numerical simulation of the behavior of l-shaped rc shear walls with staggered openings - Merabti, Salem; Guelmine, Layachi; Afkir, Mohamed; Fekir, Zineddine (Brazilian Journal of Production Engineering, 2024)
Reinforced concrete shear walls in an L-shape are highly valued in modern architecture for their ability to withstand lateral loads. However, incorporating openings, necessary for functional reasons, can compromise their structural integrity. Our study investigates the effects of offset openings on compression, tension, and shear stresses in these walls, aiming to provide design recommendations. We also analyzed shear forces and top-floor displacements in buildings with various opening configurations through numerical simulations conducted on ten-story structures. The results indicate that shear stresses increase when openings are off-center. Nevertheless, regardless of their position, the optimal proportion of openings is found to be 30% of the shear wall surface.